Малогабаритный стробоскопический блок с пониженным энергопотреблением - Ruban, V. P.; Kholod, P. V. (PE "Politekhperiodika", Book and Journal Publishers, 2003)
Ways to reduce supply voltage, lower power consumption, and minimize dimensions of the stroboscopic unit are considered. The proposed solutions allow reducing the supply voltage of the stroboscopic unit to ±5 V and decreasing the consumed current to 62.3 mA. To reduce the dimensions of the unit, it is proposed to use a strobe pulse shaper based on a slot line, which makes it possible to place the stroboscopic unit in a volume of 30×120×10 mm.